CODE SWITCHING DAN CODE MIXING DALAM KOMUNIKASI DI LINGKUNGAN DOSEN IAIN PURWOKERTO (SUATU KAJIAN SOSIOLINGUISTIK) - Muflihah Muflihah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2016)
This research was aimed at knowing the forms of code switching and code mixing found in conversations among IAIN Purwokerto lecturers and explaining the factors influencing them. This is a qualitative research in which the data to find the forms of code switching and code mixing were collected through listening to, involving in, and recording their conversation, while the to explain the factors influencing them were collected through inerviews. This research found that the forms of code mixing are word, phrase, sentence insertion; the forms of code switching are switching from local languages, Indonesian, and foreign languages. Meanwhile factors influencing code switching and code mixing are: academic mission, language improvement, meaning expression choice, solidarity, and prestige.